2021
DOI: 10.14720/aas.2021.117.2.1819
|View full text |Cite
|
Sign up to set email alerts
|

Response of hemp (Cannabis sativa L.) to integrated application of chemical and manure fertilizers

Abstract: <p>The investigation of various nutrition systems in hemp plays an influential role in improving its production. An experiment was conducted in University of Birjand, Iran, during 2013-2014, in which manure (0, 10, 20, and 30 t.ha-1 of cow manure) was considered as the main plot and the combination of nitrogen (0, 50, and 100 kg N ha-1 as urea) with phosphorus (0 and 80 kg P ha-1 as triple superphosphate) fertilizers was considered as factorial in subplots. The type of soil fertility management had no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The combination of both mineral and organic fertilizers for integrated crop nutrition as performed in our study and also cited in the literature (Bernstein et al, 2019;Da Cunha Leme Filho et al, 2020;Laleh et al, 2021) suggests that the higher availability of mineral fertilizer can be important for plant initial growth, while organic fertilizers can be employed as a more sustainable nutrient complementation during flowering without major yield losses. It is relevant to further investigate the effects of nutrient deprivation in the different stages of flowering, as the major balance between biomass accumulation and the concentration of secondary metabolites can be modulated.…”
Section: Future Outlooksupporting
confidence: 69%
“…The combination of both mineral and organic fertilizers for integrated crop nutrition as performed in our study and also cited in the literature (Bernstein et al, 2019;Da Cunha Leme Filho et al, 2020;Laleh et al, 2021) suggests that the higher availability of mineral fertilizer can be important for plant initial growth, while organic fertilizers can be employed as a more sustainable nutrient complementation during flowering without major yield losses. It is relevant to further investigate the effects of nutrient deprivation in the different stages of flowering, as the major balance between biomass accumulation and the concentration of secondary metabolites can be modulated.…”
Section: Future Outlooksupporting
confidence: 69%
“…In other studies conducted in Italy and Greece, Martinelli et al [23] and Arampatzis et al [25] observed that oil content in fruits of several milk thistle genotypes had higher values that ranged from 26.7 to 31.7% and from 24.7 to 31.1%, respectively. Compared with other species, the oil content of milk thistle is similar to hemp (Cannabis sativa L.) in which is ranging from 25.5 to 28.2% [29], but less than that in sesame (Sesamum indicum L.) and sunflower (Helianthus annuus L.) seeds that oil content is ranging from 34.2 to 36.5% and from 37.9 to 51%, respectively [30]. In 2021, the oil content in both varieties was higher compared with that in 2020, probably due to the wetter weather conditions that prevailed during April and May in 2020.…”
Section: Milk Thistle Varietiesmentioning
confidence: 96%
“…Moreover, the calcium ammonium nitrate increased the oil yield of both varieties, while sheep manure affected this parameter only in the variety Palaionterveno. Similarly, in milk thistle [16], canola (Brassica napus L.) [39], and hemp [29] crops, the application of manure increased oil yield compared to control.…”
Section: Fertilization Regimesmentioning
confidence: 99%
“…30 tons ha -1 of manure and 100 kg ha -1 of nitrogen increased leaf yield index and decreased seed yield index. Thus, hemp responds well to the combined application of nitrogen fertilizers and animal manure, while its response to P application was limited (Laleh et al, 2021). When using urea for fertilization, it is advisable to combine its application with nitrogen inhibitors, which ensure a higher yield of straw and seeds, as well as significantly reduce the rate of use of nitrogen fertilizers (Kakabouki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%